Handling of the Grievances in the National Reconstruction Authority (NRA) after the 2015 Earthquake in Nepal - Joshi, Hikmat Raj (Journal of the Institute of Engineering, 2019)
An algorithm to handle the grievances from the earthquake victims after the first processing of the data collected from them have been proposed and implemented. Suggestions to improve the performances in data collection, processing and handling have been proposed